ANALISIS MODEL ANTRIAN KEGIATAN KENDARAAN OPERASIONAL DINAS DI KABUPATEN BANYUMAS TAHUN 2020 - Khoirunnisa Salsabila; Renny Renny; Sulman Edi Supriyanto (Jurusan Matematika FMIPA Universitas Jenderal Soedirman, 2021)
Queues can occur when the need for a service exceeds the available capacity for that service. This study aims to determine the queuing model for the regional service vehicle apel activity in Banyumas Regency in 2020, the effectiveness of the number officers service, and create a simulation model of the queuing model. Based on the results of the research, it can be concluded that the queuing system at the vehicle service with two officers uses a single-phase multi-channel queue structure, queuing discipline is First Come First Served and distribution arrival is Poisson and services with Eksponensial distribution, so the queuing model used is (M/M/s). From the results of calculations using POM for windows the level of service activity is 50% of the times, the average number of apple participants in the system is 1,33 people, the average number of apple participants in the queue is 0,33 people, the average time in the system is 6,6 minutes and the average time in the queue is 1,8 minutes. Because the results of the calculation (1-r) are 50% of the break time, so the regional service vehicle apel in Banyumas Regency in 2020 officer is enough with two officers and has been effective.